Pengaruh Kemudahan Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Jasa Gojek Pada Masyarakat Di Kota Batam - Otona Zalukhu, Otona Zalukhu; Asron Saputra, Asron Saputra, S.E., M.Si. (SCIENTIA JOURNAL, 2023)
The existence of this research is to analyze the effect of convenience and service quality on the decision to purchase Gojek services in the people of Batam City. The ease of using Gojekis the most basic thing in offering products that are sold as well as the quality of service, the better the quality offered the more consumers will use it. This research uses descriptive research with a quantitative approach and the number of respondents is 212 respondents taken from the Taman Cipta Asri Tembesi housing community, Block L Rt 008 Rw 012. With the help of the SPSS version 26 program, it is found that the t count is 7.491 > t table 1.971 and the value sig 0.000 < 0.05 thus the convenience variable has a significant effect on purchasing decisions, on the service quality variable the t count is 4.005 > t table 1.971 and the sig value is 0.000 <0.05, service quality has a significant effect on purchasing decisions. The f count in this study is 104.253 > F table 2.65 and the significance is 0.000 <0.05, so the convenience and quality of service have a positive and significant effect on purchasing decisions.